Human Resource Management di Negara Berkembang: Tinjauan Komparatif dan Implikasinya bagi Reformasi Sektor Publik Indonesia - Raisa Ayu Rininta; Naufal Ageng Putera (UIR Press, 2026)
Human Resource Management (HRM) practices in developing countries are fundamentally shaped by institutional, cultural, and state capacity contexts, making it impossible for Indonesia’s public sector reform to directly adopt Western HRM models without meaningful contextual adaptation. This article aims to identify the characteristics of HRM in developing countries, compare HRM practices across regions, and analyse their implications for Indonesia’s public sector reform. A comparative literature review was conducted drawing on literature from Scopus, Web of Science, and Google Scholar databases covering the period 2013–2026. The findings indicate that HRM in developing countries is shaped by three levels of factors: national (culture, institutions, economy), contingent (ownership, organisational size, trade unions), and internal organisational (leadership, technical capacity). Cross-regional comparison reveals marked differences between East Asia’s convergence trajectory, South Asia’s dualism, Southeast Asia’s fragmentation, and Sub-Saharan Africa’s persistent patronage dominance. For Indonesia, the core challenge of HRM reform lies not merely in regulatory improvement but in entrenched bureaucratic culture, merit system inconsistency, weak institutional capacity, and persistent organisational resistance. Digital HRM transformation will only prove effective if preceded by investment in human capacity and substantive bureaucratic culture change.